Femtosecond Stimulated Raman Spectroscopy of the Cyclobutane Thymine Dimer Repair Mechanism: A Computational Study - Ando, Hideo (American Chemical Society, 2014)
[Image: see text] Cyclobutane thymine dimer, one of the major lesions in DNA formed by exposure to UV sunlight, is repaired in a photoreactivation process, which is essential to maintain life. The molecular mechanism of the central step, i.e., intradimer C—C bond splitting, still remains an open question. In a simulation study, we demonstrate how the time evolution of characteristic marker bands (C=O and C=C/C—C stretch vibrations) of cyclobutane thymine dimer and thymine dinucleotide radical anion, thymidylyl(3′→5′)thymidine, can be directly probed with femtosecond stimulated Raman spectroscopy (FSRS). We construct a DFT(M05-2X) potential energy surface with two minor barriers for the intradimer C(5)—C(5)(′) splitting and a main barrier for the C(6)—C(6)(′) splitting, and identify the appearance of two C(5)=C(6) stretch vibrations due to the C(6)—C(6)(′) splitting as a spectroscopic signature of the underlying bond splitting mechanism. The sequential mechanism shows only absorptive features in the simulated FSRS signals, whereas the fast concerted mechanism shows characteristic dispersive line shapes.